Carbon Footprint Analysis of Electrical Energy Use: Case Study Pancasila University - Anifah, Lupi; Rimantho, Dino (ASTONJADRO, 2026)
The increase in greenhouse gas (GHG) emissions due to human activities, including electricity consumption, has become a pressing global issue. This study analyzes the carbon emission footprint from electricity use at the Faculty of Engineering, Pancasila University with a quantitative approach based on an inventory of electronic devices and questionnaires. The results show that total carbon emissions reached 1,358.57975 tons of CO₂-eq/year for CO₂ compounds, 33,964.49376 tons of CO₂-eq/year for CH₄, and 404,856.7656 tons of CO₂-eq/year for N₂O. Air conditioner and lighting inventories are the largest contributors every day, reaching 2,350.78 kg CO₂/kWh for AC use and 1,226.07 kg CO₂/kWh for lighting use. The recommended strategy based on the analysis results requires energy efficiency measures and the use of renewable energy, and emphasizes the need for a green campus policy to achieve the SDGs targets.